Perlindungan Kekayaan Intelektual Batik Tradisional Dalam Perspektif Hukum - Haikal, Muhammad Firli; Faldi, Rusli; Firman, Muhammad; Noriska Salim, Maulana Rafli; Permana, Anggi; Mustaqim (Indonesian Journal of Law and Justice, 2023)
Batik is a culturally significant craft with considerable artistic merit that has permeated Indonesia. Batik featuring traditional motifs is thus a significant cultural artifact of Indonesia. Therefore, batik must be safeguarded, maintained, and its growth must be encouraged. The copyright for this batik art, which has been practiced for generations as part of a traditional culture, shall be owned by the state in accordance with Article 10, paragraph 2 of Law No. 19 of 2002 on Copyright. Nevertheless, this legislation has proven inadequate in safeguarding the intellectual property rights of conventional batik motifs during its execution. This research approach is based on an empirical legal methodology. The research findings indicate that Surakarta Kraton batik is categorized as one of the craft arts that has effectively rejuvenated its motifs, techniques, and applications, thereby ensuring its continued existence. Consequently, special protection is required, with the purpose of safeguarding traditional cultural expressions in order to prevent their extinction and preserve cultural heritage. Sui generis IPR protection is intended to safeguard folklore by ensuring that its philosophical, symbolic, theological, and sacrosanct values remain intact.